Effect of 3, 5‐Disubstitution on the Optical Properties of Luminescent 2‐(2′‐Hydroxyphenyl)benzoxazoles and Their Borate Complexes. Issue 25 (16th July 2013) - Massue, Julien; Ulrich, Gilles; Ziessel, Raymond
Abstract: This article describes the multistep synthesis and photophysical properties of three highly fluorescent dyes based on the 2‐(2′‐hydroxyphenyl)benzoxazole (HBO) scaffold and their resulting chelation to a BF2 fragment. These dyes possess functionalization at the 3, 5‐positions of the phenol ring with an ethynyl‐extended fragment bearing TMS, p ‐ t BuC6 H4, or p ‐N n Bu2 C6 H4 groups. All of the new compounds were characterized by NMR spectroscopy, mass spectrometry, and elemental analysis. The optical properties of the HBO dyes reveal the presence of enol and keto bands as a result of a strong excited‐state intramolecular proton transfer (ESIPT). This ESIPT process is highly dependent on the nature of the electronic substituents and the polarity of the solvent. Upon coordination to a BF2 fragment, typical singlet emission is observed with λ em ranging from 439 to 553 nm and quantum yields from 0.03 to 0.36. If aromatic amines are involved, strong aggregates are observed that could be dissociated upon protonation of the lone electron pair. Abstract : A series of luminescent 3, 5‐disubstituted 2‐(2′‐hydroxyphenyl)benzoxazoles (HBOs) and their corresponding borate complexes are synthesized and their optical properties investigated. HBO dyes display excited‐state intramolecular proton‐transfer fluorescence, which can be fine‐tuned depending on the substituents. Blueshifted BF2 complexes exhibit typical S0 –S1 fluorescence.